Effect of selected monoculture plantation species on the humid tropical soils of southern Nigeria - OKORO, S P A; AIGHEWI, I T; OSAGIE, C O (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted in 1997 to investigate the effect of different monoculture plantation species on some soil physical and chemical properties in the lowland rainforestr belt of south-western Nigeria, A28-year-old even-aged contiguous monoculture plantations located in Odighi, Edo state, and consisting of teak (Tectona grandis L. f), idigbo (Terminalia ivorensis A. Cher), opepe (Nauclea diderrichii Dewil and Th.Dur) and (Gmelina arborea Roxd.) and a natural forest as control were studied. The soil was a POaleudult randomly sampled in each plot at 0-2, 2-15 and 15-30 cm depth and several physical and chemical properties determined. the properties are texture, colour, pH, orgainic carbon, exchangeable cations and acidity. and effective cation exchange capacity. Data obtained was tropical forest to monoculture species resulted in signicicant loss of soil calcium and available phophorus. However, the effective cation exchange capacity,pH, magnesium content as well as texture (sand,silt and clay) of the soil were not effected by the respective plantation species. The soil organic carbon content was similarly not affected. This could be due to occurrence of frequent but different intensities of annual forest fires common in this area. Significant variation of some of there properties with depth were observed for plantation soils. Opepe plantation soil had the highest exchangeable potassium content but the lowest exchangeable aluminium content of all the monoculture plantation and natural forest soils analyzed.